Feminist Collections, v.37, no.3 (summer 2016) - (:unkn) unknown (My University, 2017)
Subtitle: A Quarterly of Women’s Studies Resources. ISSN 0742-7441, 26p.
CONTENTS: From the Editors; Book Reviews: "'A Genuine Woman’s Voice”: A New Approach to Sappho,” by Ingrid Swanberg; "Archiving Riot Grrrl & Third Wave Culture,” by Virginia Corvid; "Dancing through Labor & Delivery: The Passion of Sheila Kitzinger,” by Judith Walzer Leavitt; “Unpacking War & Conflict: Two Books about Human Security in International Relations,” by Rachel Bicicchi; “The Women of Early Modern North America: New Evidence of Vital Roles,” by Vanette Schwartz; E-Sources on Women & Gender; Periodical Notes; Books Recently Received.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews